Predicting prognosis in idiopathic pulmonary fibrosis - Barlo, N.P.; van Moorsel, C.H.M.; van den Bosch, et al., J.M.M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Idiopathic pulmonary fibrosis (IPF) is a parenchymal lung disease characterized by progressive interstitial fibrosis. In 2002, the ATS/ERS published new criteria that significantly changed the definition of IPF, resulting in a more homogeneous group of patients. IPF has a poor prognosis with a median of 2.5-3.5 years, but varying from a few months to a decade. In order to predict survival at diagnosis or during follow-up, a considerable number of studies were conducted identifying promising prognostic biomarkers. However, many had been performed before the new ATS/ERS consensus and included patients who would not meet current IPF criteria. This review provides an overview of prognostic markers of survival in IPF after the ATS/ERS consensus statement in 2002. Molecular biomarkers in serum, especially so-called pneumoproteins are relatively easy to obtain and have been independently replicated as predictors of prognosis. Cellular constituents of bronchoalveolar lavage (BAL) have been investigated as predictors of survival, but results remain contradictory. Further, a robust marker of prognosis is the change in lung function over time.However, calculating change in lung function is usually only possible over a 6-12 months period, and is therefore not useful at first presentation. The extent of fibrosis on HRCT scan and the number of fibroblast foci on lung biopsy can be measured at presentation and correlate with prognosis, but the applicability of these markers is being hampered by the lack of userand patient friendliness. In conclusion, a number of biomarkers are potential candidates for an individualised prognosis of IPF, of which so-called pneumoproteins appear most promising and should be a major focus of future research.